Analysis Of Financial Ratios On The Level Of Financial Performance Of Pt.Indofood Sukses Makmur Tbk - Ajeng Hasna Nabila; Wahyu Ramdan Kurniawan; Nita Silvia; Arti Mardianti (Westscience Press, 2023)
The goal of this study was to ascertain PT. Indofood Sukses Makmur tbk's financial performance from 2019 to 2020. Financial report data from www.IDX.co.id was used for data analysis. The ratio is a statistical method used in this study to compare large amounts of data to determine a company's financial situation over time. The liquidity ratio, represented by the current and quick ratios, and the profitability ratio, represented by the return on assets and equity, are all utilized. Between 2019 and 2020, the Liquidity Ratio as measured by the current ratio and the Quick Ratio increased. The rise happened between 2019 and 2020 due to an increase in current assets to meet obligations. Thus, PT. Indofood Sukses Makmur tbk falls within the criteria of a good company. As measured by the gross profit margin, the profitability ratio increased from 2019 to 2020, owing to the company's efficiency in utilizing assets to generate revenue, putting the company's financial health in the